PROFIL KEMAMPUAN KERJASAMA SISWA DALAM PEMBELAJARAN IPA - Indri Puspita; Tri Jalmo; Rini Rita T. Marpaung (Universitas Lampung, 2017)
This study aims were determine the profile and pattern of students cooperation ability in Science Learning on IV grade and V grade studebts. The subject in this research were 56 students from IV and V grade that were selected by using saturated sampling techniqui. The qualitative data were descriptions of the abilities and pattern of students cooperation that were obtained from students questionnaire and observation sheets that calculated the percentages and interpreted into criterias. The results showed that generaly the students cooperation ability in science learning was